Findes der skønhed i leksikografi? - Pálfi, Loránd-Levente; Wolgast, Karin; Hoff Kjeldsen, Tinne (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2019)
Loránd-Levente Pálfi, Karin Wolgast & Tinne Hoff Kjeldsen: Towards an aesthetics of lexicography In this paper, we examine a subject which has apparently never before been the object of research or published intellectual reasoning. The question is if such a thing as a beautiful dictionary or encyclopedia exists, i.e. if we can address lexicographic beauty conceived of as the sum of various inner qualities of lexicographic reference works while stripping our concept of the external properties of books such as bindings, cover, the quality of paper and print, layout, user-interface, etc. After investigating aesthetic qualities as established in other academic fields, of which mathematics and literature have been selected as representative for the purpose of developing a complementary paradigm, the article undertakes a tentative definition of lexicographic beauty.